Lazarus [videorecording (DVD)] - Scott, R. L.; Scott, R. L.; Riggs, Sean; Riggs, Sean; Mandylor, Costas, 1965-‡eactor; Brolly, Shane; Micheaux, Nicki; Smith, Stefan (Samuel Goldwyn Films, 2021)
A man is killed, but his death is a brief affair. Upon regaining consciousness, he discovers he has bee gifted with extraordinary powers that allow him to super-heroically fight the organization responsible for plunging his city into darkness.